أثر أنماط الشخصية على أداء العاملين في المنظمة دراسة حالة شركة سيرياتل للاتصالات - العيسى هزار (Latakia University Journal - Economic and Legal Sciences Series, 2018)
This study aim at exploring the effect of the different traits on the performance of the employees in syriatel Telecommunication Company to achieve the objectives of the study a questionnaire was designed to collect the data depending on the big five personality model, a total of 175 questionnaires were distributed 145 questionnaires were returned and were ready for analysis, the evaluation of the employees during 2016 was used in the statistical analysis method as a representative for employees performance, Data were analyzed using a number of statistical techniques including: the mean , frequencies and Multiple Regression, .etc. it was found that the independent variables represented by the personality traits ( extraversion ,conscientiousness) affect the dependent variable (employees performance).While the independent variables represented by the personality traits (neuroticism, agreeableness, openness) do not have a statistically significant effect. تهدف هذه الدراسة الى معرفة أثر أنماط الشخصية المختلفة على سلوك العاملين في شركة الاتصالات سيرياتل ولتحقيق أهداف الدراسة صممت استبانة لجمع البيانات بالاعتماد على نموذج العوامل الخمسة للشخصية ووزعت على عينة بلغ حجمها 175 فرد وكان عدد الاستبانات الصالحة للتحليل 145 استبانة وفي المقابل تم جمع درجة تقييم العاملين قيد الدراسة خلال الربع الأول من العام 2016 من أجل استخدامها في التحليل الاحصائي للبيانات كمؤشر على أداء العاملين ،تم اتباع عدة أساليب إحصائية تضمنت المتوسط الحسابي ،التكرارات، النسب وتحليل الانحدار المتعدد .....الخ ، وقد توصلت الدراسة الى نتائج تفيد أن المتغيرات المستقلة المتعلقة بأنماط الشخصية (الحسية، المتفانية) لها أثر إيجابي على المتغير التابع وهو سلوك العاملين أصحاب هذه الأنماط بينما المتغيرات المستقلة المتعلقة بأنماط الشخصية (الانفعالية،القبولية،المنفتحة ) ليس لها أثر ذو دلالة احصائية.